Update in New Anabolic Therapies for Osteoporosis - Canalis, Ernesto (The Endocrine Society, 2010)
Skeletal anabolic agents enhance bone formation, which is determined by the number and function of osteoblasts. Cell number is controlled by factors that regulate the replication, differentiation, and death of cells of the osteoblastic lineage, whereas cell function is controlled by signals acting on the mature osteoblast. Bone morphogenetic proteins (BMP) and Wnt induce the differentiation of mesenchymal cells toward osteoblasts, and IGF-I enhances the function of mature osteoblasts. The activity of BMP, Wnt, and IGF-I is controlled by proteins that, by binding to the growth factor or to its receptors, can antagonize its effects. Changes in the expression or binding affinity of these extracellular antagonists can be associated with increased or decreased bone formation and bone mass. Novel approaches to anabolic therapies for osteoporosis may include the use of factors with anabolic properties, or the neutralization of a growth factor antagonist. Selected approaches include the use of neutralizing antibodies to Wnt antagonists, the enhancement of BMP signaling by proteasome inhibitors, or the use of activin soluble receptors, IGF-I, or PTH analogs. An anabolic agent needs to be targeted specifically to the skeleton to avoid unwanted nonskeletal effects and ensure safety. Clinical trials are being conducted to test the long-term effectiveness and safety of novel bone anabolic agents.